2006
DOI: 10.1016/j.foodchem.2004.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced pH and thermal stabilities of invertase immobilized on montmorillonite K-10

Abstract: Invertase was adsorbed onto micro-porous acid-activated montmorillonite clay (K-10) by two procedures, namely adsorption and covalent binding. The immobilized enzymes were characterized by XRD, surface area measurements and 27 Al NMR. XRD measurements revealed an expansion of clay layers due to immobilization which suggests that intercalation had taken place. Surface area measurements also support this observation. 27 Al NMR showed that interaction of enzyme with tetrahedral and octahedral Al changes with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 22 publications
8
46
0
2
Order By: Relevance
“…2, it can be observed that all immobilized enzymes retained more than 80 of their relative activity over a broader temperature range from 45 to 55 with a 10 increase in optimum temperature compared to the free enzyme. Similar observations have reported that the immobilization increased the temperature optimum from 50 to 60 23 . Bornscheuer 25 reported that the shift in optimal temperature toward higher values could be due to the immobilization of the enzyme.…”
Section: Degumming Of Soybean Oilsupporting
confidence: 89%
“…2, it can be observed that all immobilized enzymes retained more than 80 of their relative activity over a broader temperature range from 45 to 55 with a 10 increase in optimum temperature compared to the free enzyme. Similar observations have reported that the immobilization increased the temperature optimum from 50 to 60 23 . Bornscheuer 25 reported that the shift in optimal temperature toward higher values could be due to the immobilization of the enzyme.…”
Section: Degumming Of Soybean Oilsupporting
confidence: 89%
“…One of the main reasons for enzyme immobilization is the anticipated increase in its stability to various deactivating forces due to restricted conformational mobility of the molecules following immobilization. Therefore, the immobilized enzyme could work in harsh environmental conditions with less activity loss compared to the free counterpart [1,[17][18][19].…”
Section: Relative Activity (%)mentioning
confidence: 99%
“…In contrast to this study, bioaffinity-based immobilization of almond (A. communis) b-galactosidase on Con A-layered calcium alginate-cellulose beads [30] and b-galactosidase (A. oryzae) immobilized on Con A-celite 545 [32] showed that both immobilized and soluble enzyme showed an optimum activity at 50°C. For this reason, the immobilized enzyme could work in wild environmental conditions with less activity loss compared to its soluble counterpart [42][43][44].…”
Section: Effect Of Phmentioning
confidence: 99%